Left ventricular ejection fraction is associated with prevalent and incident cardiovascular disease in patients with intermittent claudication – results from the CAVASIC Study. Issue 2 (April 2015) - Rantner, Barbara; Pohlhammer, Johannes; Stadler, Marietta; Peric, Slobodan; Hammerer-Lercher, Angelika; Klein-Weigel, Peter; Fraedrich, Gustav; Kronenberg, Florian; Kollerits, Barbara
Abstract Background Individuals with an impaired ventricular function have a poor prognosis due to underlying heart failure and higher mortality rates. Patients with peripheral arterial disease (PAD) represent a high-risk population for left ventricular systolic dysfunction (LVSD). Methods The left ventricular ejection fraction (LVEF) was measured in a subset of the CAVASIC Study, consisting of 180 male patients with intermittent claudication and 226 controls. The patients were prospectively followed for a median time of 7 years. The association of LVEF with PAD and prevalent cardiovascular disease (CVD) as well as with incident CVD and survival rates during follow-up was analyzed. Results The prevalence of LVSD (LVEF<55%) was 30% among PAD patients and 7% among controls (p < 0.001). The adjusted logistic regression analysis showed that a decrease of LVEF by one standard deviation (SD) and an LVEF below 55% was associated with PAD (OR = 1.72, 95%CI 1.30–2.28 and OR = 5.71, 95%CI 2.52–12.95, both p < 0.001). Similar results were found for prevalent CVD (n = 50) in PAD patients: LVEF per SD: OR 1.60; LVEF <55%: OR 2.81, both p ≤ 0.008. The adjustment for ln-NT-proBNP or hs-cTnT resulted in a borderline significant association. In the adjusted Cox regression analysis a decrease of LVEF by one SD showed a trend for association with all-cause mortality (n = 32) (HR 1.27, p = 0.08). An impaired LVEF significantly increased the risk for incident major CVD events (n = 52): HR 1.56, p < 0.01. Conclusions Patients with PAD have significantly lower LVEF values compared to controls. The LVEF can serve as a risk predictor for subsequent cardiovascular disease among this high-risk population.